2014
DOI: 10.1038/bjc.2014.147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HER2 copy number in IHC2+/FISH-amplified breast cancer on outcome of adjuvant trastuzumab treatment in a large UK cancer network

Abstract: Background:Adjuvant trastuzumab with chemotherapy is standard treatment for HER2-positive breast cancer, defined as either HER2 IHC3+ or IHC2+ and FISH amplified. The aim of this study was to investigate the degree to which HER2 amplification in terms of HER2 gene copy numbers in HER2+IHC2+ cancers affected the outcome in a community setting.Methods:Case records of 311 consecutive patients with early breast cancer presenting between 1st January 2005 and 31st December 2008 were reviewed. Progression-free surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Compared with the present study including 886 cases, one smaller-scale study conducted in patients presenting between 2005 and 2008 did not reveal a significant survival difference between 163 HER2 IHC 3+ patients and 59 IHC 2+/ISH+ patients receiving adjuvant trastuzumab therapy. 8 However, similar to our results, IHC 2+/ISH+ patients with high HER2 copy numbers (>12) had better survival rates than did those with intermediate HER2 copy numbers (6-12) (it was not possible to analyse P-values). 8 As the study cohorts were different, the cut-off value of HER2 signals to define a high HER2 copy number for the other study was different from that used in our study (≥8).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Compared with the present study including 886 cases, one smaller-scale study conducted in patients presenting between 2005 and 2008 did not reveal a significant survival difference between 163 HER2 IHC 3+ patients and 59 IHC 2+/ISH+ patients receiving adjuvant trastuzumab therapy. 8 However, similar to our results, IHC 2+/ISH+ patients with high HER2 copy numbers (>12) had better survival rates than did those with intermediate HER2 copy numbers (6-12) (it was not possible to analyse P-values). 8 As the study cohorts were different, the cut-off value of HER2 signals to define a high HER2 copy number for the other study was different from that used in our study (≥8).…”
Section: Discussionsupporting
confidence: 86%
“…8 However, similar to our results, IHC 2+/ISH+ patients with high HER2 copy numbers (>12) had better survival rates than did those with intermediate HER2 copy numbers (6-12) (it was not possible to analyse P-values). 8 As the study cohorts were different, the cut-off value of HER2 signals to define a high HER2 copy number for the other study was different from that used in our study (≥8). In a study of metastatic breast cancer, high HER2 copy numbers (>13) were associated with a short time-to-metastasis; however, patients responded well to trastuzumab-based therapy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…From our data analysis, it was clear that the current ASCO guidelines for HER2/CEP17 ratio and copy number has a poor PPV. It is possible that using higher cut-off values might reduce the number of luminal tumors selected; some authors have reported a better response to trastuzumab with copy number > 12 28 and higher HER2/CEP17 ratio, 29 although the HER2E tumors in this series have copy numbers ranging from 6.55 to 19.05 and HER2/CEP17 ratios from 3.17 to 6.68.…”
Section: Discussionmentioning
confidence: 81%
“…Some tumours reported as HER2 positive are subtyped as Luminal B and retain some responsiveness to endocrine treatment in addition to chemotherapy and HER2 targeted treatments. 4 Borley et al 5 demonstrated that the HER2 gene copy number provides additional information for stratifying breast cancer patients into different treatment groups, because HER2-positive patients with a low degree of HER amplification were shown to derive less benefit from trastuzumab (the chemotherapy agent more commonly known as Herceptin ® ).…”
Section: Introductionmentioning
confidence: 99%